DUPLICATION OF THE SHORT ARM OF THE X-CHROMOSOME IN MOTHER AND DAUGHTER - Tuckmuller, C. M.; Martinez, J. E.; Batista, DAS; Kearns, W. G.; Wertelecki, W. (Springer, 1993)
An 11-year-old girl with short stature, mental retardation, and mild dysmorphic features was found to have an inverted duplication of most of the short arm of the X chromosome [dic inv dup(X)(qter --> p22.3 = p22.3 --> cen:)]. Her mother, who is also short and retarded, carries the same duplication. Fluorescence in situ hybridization with an X chromosome library, and with X centromere-specific alpha satellite and telomere probes, was useful in characterizing the duplication. In most females with structurally abnormal X chromosomes, the abnormal chromosome is inactivated. Although the duplicated X was consistently late replicating in the mother, X chromosome inactivation studies in the proband indicated that in 11 % of her lymphocytes the duplicated X was active.